The Outcome of Fetal Reduction in High Order Multiple Pregnancy - AlKhalidi, Batool A. Hashim (Medical Science Journal for Advance Research, 2026)
Background: High-order multiple pregnancies, is rising in incidence owing to rising incidence of assisted reproduction -conceived pregnancies, thus, start to emerge as a not infrequently seen challenge in our daily gyn/ob- daily clinical practice. The term of high order multifetal pregnancy is applied to gestation involving three or more fetuses, and is associated with significant maternal and neonatal complications, largely due to increased rates of preterm birth and low birth weight. Multifetal pregnancy reduction has been proposed as a strategy to improve perinatal outcomes, the technique was introduced in our middle Euphrates governorates (including Annajaf AlAshraf) relatively only recently, and its acceptance is still questionable among ART physicians. In this paper we try to show our patients series outcomes for all procedure done in our private center since it was first introduced in 2021 till the time we accomplished this paper. Objective: the aim of the study is to express maternal and neonatal outcomes of all high-order multiple pregnancies underwent multifetal reduction management to twin pregnancies, including our own figure of procedure- related pregnancy loss rate. Methods: This retrospective cohort study included 15 women with triplet or quadruplet pregnancies diagnosed before 10 weeks of gestation and managed at Al –Ameer assisted reproduction center in Annajaf Al-Ashraf province in Iraq managed with fetoreduction at 9-10 weeks of gestation having their pregnancies followed in collaboration with Al-Zahraa Maternity and Children's Teaching Hospital a teaching center affiliated to medical school of Kufa university, from January 2021 to September 2024. Maternal and neonatal outcomes, including gestational age at delivery, perinatal complications, birth weight, Apgar scores, maternal complications, and our own figure of intervention- associated pregnancy loss rate were all assessed in numbers and percentages. Results: of 15 collected sample studied 8 women were of the age group(25.1–30years), all the 15 were in their 1st pregnancy( primigravidae), 13 were with triplets and two of 15 with quadruplets, all of them were already diagnosed and are treated by fetoreduction 9-10 weeks, 11/15(73.3%) delivered at term, 13.3 % delivered at late preterm gestational age(35-36 weeks), 6.6% delivered at very preterm (29 weeks), 6.6% aborted at 18 weeks due to covid infection, there was no perinatal deaths of those reached potential viable pregnancy stage(14/14) with all live births had survived, with their Apgar Scores; 6.70 ± 1.77& 8.00 ± 3.97 at 1&5 minutes respectively, 21.4%(3/14) of reduced pregnancies developed preterm birth with or without prelabour rupture of fetal membranes all survived, our own procedure- related pregnancy loss rate is 0%.Conclusion: Fetoreduction in high-order multiple pregnancies appears to improve neonatal outcomes and reduce maternal complications, particularly preterm delivery and perinatal death. The study shows that fetoreduction is an effective management option in high-order multiple pregnancies even though it leads to more cesarean deliveries. To confirm these findings and improve clinical practices, more prospective studies across multiple centers are needed.